Application of AOA algorithm for optimal placement of electric vehicle charging station to minimize line losses - Kathiravan, K.; Rajnarayanan, P.N. (Electric power systems research, 2023)
•Placement of electric vehicle charging station (EVCS).•Distributed generations (DGs) are integrated with EVCS.•Power loss minimization.•Arithmetic optimization algorithm.•Distribution network. The conventional transportation system uses fossil fuels and it emits greenhouse gases which affect the environment. A new kind of transportation must be created immediately because of the growing population. Electric Vehicles (EVs) have less impact on environmental pollution and they will become the base for future transport systems. The battery's specific energy is very low and it needs frequent charging. The long-distance transportation using EVs needs charging stations and it leads to placing Electric Vehicle Charging Station (EVCS) in the power grid. The placement of EVCS in the grid increases network losses which have an adverse impact on the grid. In this research work, network loss minimization by the optimum placement of EVCS along with Distributed Generation (DG) is considered. The proposed approach has been validated on the IEEE 33 bus system. The analysis was carried out using the Loss Sensitivity Factor (LSF) approach considering the variable network parameters in the Radial Distribution Network (RDN). The EVCS optimal placement was resolved by Arithmetic Optimization Algorithm (AOA). The results are compared with Particle Swarm Optimization (PSO) and Harris Hawks Optimization (HHO) approaches. The findings show that the optimal placement of EVCS along with DGs reduces network losses considerably.